Problems of Private Law Protection of Competition in the EC Law - V. A. Gorbachev (Московский журнал международного права, 2009)
The European Court of Justice recalled in its decisions in 2001 and 2006 that any citizen or business who suffers harm as a result of a breach of EC antitrust rules (Articles 81 and 82 of the EC Treaty) must be able to claim reparation from the party who caused the damage. This right of victims to compensation is guaranteed by Community law. However, despite the requirement to establish an effective legal framework turning exercising the right to damages into a realistic possibility, to date in practice victims of EC antitrust infringements only rarely obtain reparation of the harm suffered. The article considers the newest tendencies of the EC antitrust legislation and policy, courts decisions in the field of private actions for compensation of damages to the parties suffered from illegal agreements, actions and behavior that falls within the Articles 81 and 82 of the EC Treaty.